In vivo and in vitro genome editing to explore GNE functions - Ilouz, Nili; Harazi, Avi; Guttman, Miriam; Daya, Alon; Ruppo, Shmuel; Yakovlev, Lena; Mitrani-Rosenbaum, Stella (Frontiers in Genome Editing, 2022)
GNE myopathy is an adult onset neuromuscular disorder characterized by slowly progressive distal and proximal muscle weakness, caused by missense recessive mutations in the GNE gene. Although the encoded bifunctional enzyme is well known as the limiting factor in the biosynthesis of sialic acid, no clear mechanisms have been recognized to account for the muscle atrophic pathology, and novel functions for GNE have been hypothesized. Two major issues impair studies on this protein. First, the expression of the GNE protein is minimal in humans and mice muscles and there is no reliable antibody to follow up endogenous expression. Second, no reliable animal model is available for the disease and cellular models from GNE myopathy patients' muscle cells (expressing the mutated protein) are less informative than expected. In order to broaden our knowledge on GNE functions in muscle, we have taken advantage of the CRISPR/Cas9 method for genome editing to first, add a tag to the endogenous Gne gene in mouse, allowing the determination of the spatiotemporal expression of the protein in the organism using well established and reliable antibodies against the specific tag. In addition we have generated a Gne knock out murine muscle cell lineage to identify the events resulting from the total lack of the protein. A thorough multi-omics analysis of both systems including transcriptomics, proteomics, phosphoproteomics and ubiquitination, unraveled novel pathways for Gne, in particular its involvement in cell cycle control and in the DNA damage/repair pathway. The elucidation of fundamental mechanisms of Gne in normal muscle may contribute to the identification of the disrupted functions in GNE myopathy, thus, to the definition of novel biomarkers and possible therapeutic targets for this disease.